2013
DOI: 10.1103/physrevlett.110.041301
|View full text |Cite
|
Sign up to set email alerts
|

Search for Photon-Linelike Signatures from Dark Matter Annihilations with H.E.S.S.

Abstract: Gamma-ray line signatures can be expected in the very-high-energy (E(γ)>100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼ 500 GeV and ∼ 25 TeV for the central pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
386
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(391 citation statements)
references
References 25 publications
4
386
1
Order By: Relevance
“…6 The details of our factorization theorem, which is identical to the wino result, can be found in [7,8]. Because of the more involved operator structure, we will also decompose 6 Strictly speaking, O2 in eq. (3.1) contains a fifth collinear structure, which we could call O e c = BD BD.…”
Section: Jhep03(2016)213mentioning
confidence: 90%
See 1 more Smart Citation
“…6 The details of our factorization theorem, which is identical to the wino result, can be found in [7,8]. Because of the more involved operator structure, we will also decompose 6 Strictly speaking, O2 in eq. (3.1) contains a fifth collinear structure, which we could call O e c = BD BD.…”
Section: Jhep03(2016)213mentioning
confidence: 90%
“…The possibility of such experiments to set stringent limits on the wino scenario was explored in [2,5]. By combining a numerical calculation of the Sommerfeld enhancement with a tree-level annihilation of WIMPs to γγ + 1 2 γZ, they found that the HESS experiment ruled out the wino by a factor of 15 under the assumption of an NFW dark matter halo profile [6]. In particular though, [5] extended their annihilation calculation to one-loop and found a reduction in rate by ∼ 4× at the thermal relic mass of 3 TeV.…”
Section: Jhep03(2016)213mentioning
confidence: 99%
“…[63]. The Fermi -LAT upper limits on σ ann v extend from ∼10 −29 cm 3 s −1 at m χ = 10 GeV to ∼10 −27 cm 3 s −1 at m χ = 300 GeV, while the H.E.S.S.…”
Section: Annihilationmentioning
confidence: 99%
“…This is why this feature has been so appealing, and many searches for a hint of it have been conducted so far, in galaxy clusters [60], Milky Way dSph satellites [61], and in the GC and Halo [62,63]. In addition, it is worth mentioning that there is a recently claimed hint of a line-like signal at ∼130 GeV in the Fermi -LAT data of the GC region [40,64]: if the observed signal originates from direct DM annihilation into two photons, the WIMP particle should have a mass of m χ = 129±2.4 +7 −13 GeV and an annihilation rate (assuming the Einasto profile) of σ ann v γγ = (1.27± 0.32 +0.…”
Section: Gamma-ray Linesmentioning
confidence: 99%
See 1 more Smart Citation